Hazardous waste management in South African mining: a CGE analysis of the economic impacts - Manfred Wiebelt (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1999)
There is no doubt that an improved hazardous waste management in mining and mineral processing will reduce environmental and health risks in South Africa. However, skeptics fear that waste reduction, appropriate treatment and disposal are not affordable within the current economic circumstances, neither from an economic nor from a social point of view. This paper mainly deals with the first aspect and touches upon the second. It investigates the short-run and long-run sectoral impacts of an environmental tax on hazardous waste in South African mining using an open-economy multisectoral general equilibrium model. The results bear out the expectation that the possibilities for shifting higher production costs are limited in an open economy. Moreover, the results show that the brunt of adjustment of an isolated approach towards hazardous waste management has to be beared by black workers.
Keywords: D58; Q2; O55; 330; environmental management; mining and minerals processing; CGE analysis; South Africa; Sonderabfall; Abfallabgabe; Bergbau; Umweltpolitik; Wirtschaftspolitische Wirkungsanalyse; Allgemeines Gleichgewicht; Social Accounting Matrix; Südafrika